Note sur la présence de Perna perna L. (= Mytilus africanus Chemnitz) dans la region de Bizerte (Tunisie): Etude quantitative du peuplement - ZAOUALI, Jeanne (INSTM Bulletin : Marine and Freshwater Sciences, 1973)
2 habitats of this sp, of vast geographic distribution, have been seen in the south region of Bizerte, where together with Mytilus galloprovincialis, they live in dense colonies attached to Cystoseira sedioides. Perna perna has also been found in the Lake of Bizerte. A quantitative study has been conducted.